2003
DOI: 10.1080/00140130303534
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal feedback: an assessment of performance and mental workload

Abstract: Multimodal interfaces offer great potential to humanize interactions with computers by employing a multitude of perceptual channels. This paper reports on a novel multimodal interface using auditory, haptic and visual feedback in a direct manipulation task to establish new recommendations for multimodal feedback, in particular uni-, bi- and trimodal feedback. A close examination of combinations of uni-, bi- and trimodal feedback is necessary to determine which enhances performance without increasing workload. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 17 publications
6
104
2
Order By: Relevance
“… Furthermore, since the information is delivered sequentially, any interfering effects that could happen in parallel transmission (when two modalities distract from one another) are avoided [87].…”
Section: Advantagesmentioning
confidence: 99%
“… Furthermore, since the information is delivered sequentially, any interfering effects that could happen in parallel transmission (when two modalities distract from one another) are avoided [87].…”
Section: Advantagesmentioning
confidence: 99%
“…On the other hand, our sense of touch is much more limited, with an intensity range of approximately 55dB above the detection threshold. Any vibrations above this threshold feel unpleasant or even painful [150].…”
Section: Intensitymentioning
confidence: 99%
“…Thus, a large body of works showed that the audio channel is a very appropriate modality for notification of changes (see [17,24] for examples). Combined with graphics, sound is also supposed to support users in direct manipulation interaction by enhancing the perception of their actions [6,13,20].…”
Section: Enhancing Perceptionmentioning
confidence: 99%